Leadership styles and safety performance: role of employee’s attitude towards safety as mediator / Nurul ‘Izzah Muhamad Noh - Muhamad Noh, Nurul ‘Izzah (2014)
The quality of a leader is an important factor for any organization as it will affect safety performance. Accidents at workplace can be prevented if employee are more sensitive and have good safety attitude.The purpose of this study is to examine the relationship between leadership styles which are transformational leadership and transactional leadership with safety performance mediated by employee attitude towards safety. This study was carried out at SMEs manufacturing chemical in northern region of Malaysia. In this study researcher has distributed a set of questionnaire to employees at the operational level. The number of sample size is 313 respondents. 450 questionnaires were distributed, where only 252 were returned back. Using hierarchical multiple regression analysis, the result show that two dimensions namely idealized influence and inspirational motivation are found to have significant relationship with safety performance mediated by employee attitude towards safety. The result of this study supports the objectives of this study that employee attitude towards safety mediated the relationship between leadership styles and safety performance. In addition, the result of this study also confirms the integrated dimensions of transformational leadership consist of idealized influence, inspirational motivation, intellectual stimulation, individualized consideration and moral modeling. The expected significant contribution from this study is a thorough understanding of leadership style and role of employee attitude towards safety explain safety performance. The outcome of this study can also be used as a guide to provide an approach for leaders in implementing effective safety management in SMEs.